2021
DOI: 10.1080/10717544.2021.1898703
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled polymeric nanocarrier-mediated co-delivery of metformin and doxorubicin for melanoma therapy

Abstract: Malignant melanoma is a life-threatening form of skin cancer with a low response rate to single-agent chemotherapy. Although combined therapies of metformin (MET) and doxorubicin (DOX) are effective in treating a variety of cancers, including breast cancer, their different physicochemical properties and administration routines reduce the effective co-accumulation of both drugs in tumors. Nanoparticles (NPs) have been demonstrated to potentially improve drug delivery efficiency in cancer therapy of, for example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 56 publications
0
32
0
Order By: Relevance
“…At present, there are many options for achieving tumor-targeted gene delivery. For example, our previous work mainly focused on passive targeting through the enhanced permeability and retention (EPR) effect or through cancer cellspecific ligands (such as antibodies, peptides, and surface mountants) [111,112]. Active targeting enhances the targeting ability of NPs to maximize tumor distribution and deep tissue penetration.…”
Section: Tumor Targetingmentioning
confidence: 99%
See 3 more Smart Citations
“…At present, there are many options for achieving tumor-targeted gene delivery. For example, our previous work mainly focused on passive targeting through the enhanced permeability and retention (EPR) effect or through cancer cellspecific ligands (such as antibodies, peptides, and surface mountants) [111,112]. Active targeting enhances the targeting ability of NPs to maximize tumor distribution and deep tissue penetration.…”
Section: Tumor Targetingmentioning
confidence: 99%
“…Polymer NPs play a central role in a variety of applications, such as drug delivery, medical imaging, and the early detection of disease [126][127][128]. Polymer NPs are particles obtained from natural (chitosan [129], sodium alginate [111] and cyclodextrin [130], etc. ), semi-synthetic or synthetic polymers (poly(lactic-co-glycolic acid)poly(ethylene glycol) (PLGA-PEG) [131], N-(2-hydroxypropyl)methacrylamide (HPMA) [132] and poly(acrylamide) (PAM) [133]).…”
Section: Polymer Npsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports have identified nanomedicine as an ideal approach to improve the efficiency and wound treatment. 3 Nanoparticles are ultrafine particles between 1–1000 nm in diameter, 8 that have many advantageous properties related to trauma therapy, including being biodegradable, exhibiting controlled drug release, enough drug delivery efficacy, 10 have healing properties, penetrated blood-brain barrier 11 and their ability to be used as an extracellular matrix material. 3 Many studies have shown that nanoparticles can improve antibacterial and wound-healing activities.…”
Section: Introductionmentioning
confidence: 99%